2010
DOI: 10.2131/jts.35.749
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to titanium dioxide nanoparticles increases dopamine levels in the prefrontal cortex and neostriatum of mice

Abstract: -Titanium dioxide (TiO 2 ) nanoparticles are widely used in cosmetics, sunscreen and as a photocatalyst. However, little is known about the biological effect of TiO 2 nanoparticles in humans and other animals. Here, we investigated whether prenatal exposure to TiO 2 nanoparticles impacted the central nervous system in mice. We measured the levels of dopamine (DA) and its metabolites in several regions of the brain in mice using high performance liquid chromatography (HPLC). HPLC analysis showed that DA and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 30 publications
5
72
1
1
Order By: Relevance
“…This result highlights the possibility that prenatal exposure to TiO 2 NPs might affect the development of the central dopaminergic system in mouse offspring. 44 Shimizu et al 45 also found that maternal exposure to TiO 2 NPs influenced the expression of functional genes related to brain development in mice. Similar in vivo studies showed that prenatal exposure to TiO 2 NPs affects the synaptic plasticity in the offspring's hippocampal dentate gyrus area, revealing the hidden toxicity of TiO 2 NPs in CNS.…”
mentioning
confidence: 98%
“…This result highlights the possibility that prenatal exposure to TiO 2 NPs might affect the development of the central dopaminergic system in mouse offspring. 44 Shimizu et al 45 also found that maternal exposure to TiO 2 NPs influenced the expression of functional genes related to brain development in mice. Similar in vivo studies showed that prenatal exposure to TiO 2 NPs affects the synaptic plasticity in the offspring's hippocampal dentate gyrus area, revealing the hidden toxicity of TiO 2 NPs in CNS.…”
mentioning
confidence: 98%
“…Nanoparticles were found in the brain, and they induced apoptotic changes in the olfactory bulb in the prenatally exposed male offspring six weeks after the prenatal exposure . A comparable exposure increased levels of dopamine in the offspring brain (Takahashi et al, 2010). In addition, gene expression was altered in the offspring brain related to development and function of the central nervous system.…”
Section: Developmental Neurotoxicitymentioning
confidence: 93%
“…Adverse effects of prenatal exposure to engineered nanoparticles in vitro and in vivo have been summarized by (Ema et al, 2010;Hougaard et al, 2011). The effects observed in animals include altered immune response, development of the nervous system and reproductive function (Fedulov et al, 2008;Lamoureux et al, 2010;Shimizu et al, 2009;Takahashi et al, 2010;Takeda et al, 2009;Yoshida et al, 2009;Yoshida et al, 2010).…”
Section: Ambient Air Pollutionmentioning
confidence: 99%
“…ZnO NPs were suspended at 0.5 mg/ml, and 0.2 ml was administrated subcutaneously to the pregnant ICR mice at GD 5, 8, 11, 14, and 17 (100 μg/mouse/day: total 500 μg/mouse). Administered ZnO NPs was same as the mass dose in the previous study about the effects of prenatal TiO 2 NP exposure on dopaminergic system (Takahashi et al, 2010). Control mice were treated with saline containing 0.05% Tween-80.…”
Section: Animalsmentioning
confidence: 99%